The The effect of purchase price of oil palm fresh fruit bunches (FFB) on fertilization frequency (case study: Mamuju Regency, West Sulawesi) - Hajrah, Siti; Makmur, Makmur; Damrah, Fatmawaty; Karim, Ikawati (Anjoro: International Journal of Agriculture and Business, 2021)
The purchase price of oil palm has often experienced significant increases and decreases due to several factors including oil palm production, oil palm exports, and the oil palm price. Fertilization is one of the most important and complex technical culture activities in oil palm farming. Fertilization in oil palm plants should be able to guarantee normal vegetative and generative growth to provide optimal Fresh Fruit Bunches (FFB) production and produce high quality and quantity of crude palm oil. This study aims to evaluate how much influence the FFB purchase price has on the frequency of fertilization used by oil palm farmers. This research is a quantitative study with a descriptive analysis design to see the effect of the purchase price of fresh fruit bunches on the frequency of fertilization used by oil palm farmers in the Mamuju Regency. The results of regression analysis data showed that the purchase price of FFB influenced the frequency of oil palm fertilization by 11.3 percent.